VA opsin-based photoreceptors in the hypothalamus of birds. - Halford, S; Pires, S; Turton, M; Zheng, L; González-Menéndez, I; Davies, W; Peirson, S; García-Fernández, J; Hankins, M; Foster, R (2009)
Studies in the 1930s demonstrated that birds possess photoreceptors that are located within the hypothalamus and regulate photoperiodic responses to day length. Most recently, photoperiod has been shown to alter the activity of the pars tuberalis to release thyrotrophin, which ultimately drives a reproductive response. Despite these significant findings, the cellular and molecular identity of the hypothalamic photoreceptors has remained a mystery. Action spectra implicated an opsin-based photopigment system, but further identification based on rod- or cone-opsin probes failed, suggesting the utilization of a novel opsin. The vertebrate ancient (VA) opsin photopigments were isolated in 1997 but were thought to have a restricted taxonomic distribution, confined to the agnatha and teleost fish. Here, we report the isolation of VA opsin from chicken and show that the two isoforms spliced from this gene (cVAL and cVA) are capable of forming functional photopigments. Further, we show that VA opsin is expressed within a population of hypothalamic neurons with extensive projections to the median eminence. These results provide the most complete cellular and molecular description of a deep brain photoreceptor in any vertebrate and strongly implicate VA opsin in mediating the avian photoperiodic response.